Understanding the Effects of Sublethal Pesticide Exposure on Honey Bees: A Role for Probiotics as Mediators of Environmental Stress - Chmiel, John A.; Daisley, Brendan A.; Pitek, Andrew P.; Thompson, Graham J.; Reid, Gregor (Frontiers in Ecology and Evolution, 2020)
Managed populations of the European honey bee (Apis mellifera) support the production of a global food supply. This important role in modern agriculture has rendered honey bees vulnerable to the noxious effects of anthropogenic stressors such as pesticides. Although the deleterious outcomes of lethal pesticide exposure on honey bee health and performance are apparent, the ominous role of sublethal pesticide exposure is an emerging concern as well. Here, we use a data harvesting approach to better understand the toxicological effects of pesticide exposure across the honey bee life cycle. Through compiling adult- and larval-specific median lethal dose (LD50) values from 93 published data sources, LD50 estimates for insecticides, herbicides, acaricides, and fungicides are highly variable across studies, especially for herbicides and fungicides, which are underrepresented in the meta-data set. Alongside major discrepancies in these reported values, further examination of the compiled data suggested that LD50 may not be an ideal metric for honey bee risk assessment. We also discuss how sublethal effects of pesticide exposure, which are not typically measured in LD50 studies, can diminish honey bee reproduction, immunity, cognition, and overall physiological functioning, leading to suboptimal honey bee performance and population reduction. In consideration of actionable solutions to mitigate the effects of sublethal pesticide exposure, we have identified the potential for probiotic supplementation as a promising strategy that can be easily incorporated alongside current agricultural infrastructure and apicultural management practices. Probiotic supplementation is regularly employed in apiculture but the potential for evidence-based targeted approaches has not yet been fully explored within a formal toxicological context. We discuss the benefits, practical considerations, and limitations for the use and delivery of probiotics to hives. Ultimately, by subverting the sublethal effects of pesticides we can help improve the long-term survival of these critical pollinators.